Imagens, sentidos e TDAH: representações sociais dos professores acerca da inclusão de alunos com Transtorno de Déficit de Atenção e Hiperatividade na Amazônia Bragantina - RIBEIRO, Carla Talita Alves (2021)
The present study aims to analyze the social representations of the professors of the Caetés region about the student with ADHD and the implications in teaching practice in the Amazon region. As theoretical-methodological support, we adopted the theory of social representations from the tridimensionality of Moscovici: concept, images and attitudes for the construction of a representational field, in which each dimension was configured as a structure Conducting and field of analysis, where the objections and anchorages constituting this representation were highlighted. The study included 05 teachers who work in the elementary school of the city of Bragança-PA. The problem investigated and what are the processes that constitute the social representations of teachers about the practice of teaching for students with ADHD? For the study, the following instruments were used: a) socio-demographic questionnaire; b) Free Word association (TALP) test; and c) Semi-structured interview script. The research is of a qualitative and descriptive nature. The results show that the teachers are fundamental pieces in this process of inclusion, from the teaching learning of students, to overcome the difficulties encountered through the disorder, to search for strategies, where the professors are the mediators of the Knowledge, always seeking innovation and commitment to develop their classes. We have come to the conclusion that teachers need to know the student with ADHD, and not only the disorder and through pedagogical interventions, help these students to overcome the difficulties, potentializing their abilities